The use of Bruch's membrane opening-based optical coherence tomography of the optic nerve head for glaucoma detection in microdiscs - Enders, Philip; Schaub, Friederike; Adler, Werner; Nikoluk, Roman; Hermann, Manuel M.; Heindl, Ludwig M. (British Journal of Ophthalmology, 2017)
PURPOSE: To assess the performance of Bruch's membrane opening (BMO)-based spectral domain optical coherence tomography (SD-OCT) of the optic nerve head for glaucoma detection in microdiscs in comparison with confocal scanning laser tomography (CSLT). DESIGN: Retrospective cohort study. METHODS: 82 eyes of 82 patients with disc size <1.63 mm2 underwent SD-OCT and CSLT measurements, visual field testing and clinical examination. BMO-based minimal rim width (BMO-MRW), retinal nerve fibre layer thickness (RNFLT) in SD-OCT and rim area measured in CSLT were compared and correlated with visual field defects. RESULTS: 51 patients with glaucoma, 11 patients with ocular hypertension (OHT) and 20 healthy controls had a mean disc area of 1.36±0.19 mm2 in CSLT, and BMO area was 1.45±0.22 mm2 (r=0.17; p=0.12). In patients with glaucoma, visual field mean defect was -7.5±6.7 dB. Global BMO-MRW correlated better with visual field function (Spearman's r=0.65; p<0.001) than RNFLT (r=0.58; p≤0.001) and CSLT rim area (r=0.47; p=0.004). BMO-MRW significantly deteriorated with progressive visual field loss (p<0.001). In receiver operating characteristic analysis, sensitivity of BMO-MRW was 68.6% at 95% specificity (area under curve (AUC)=0.87), similar to sensitivity of RNFLT (66.4%; AUC=0.81). Performance of CSLT rim area was significantly worse (AUC=0.70, p=0.008). In healthy controls, mean BMO-MRW was 344.3±64.1 µm, mean RNFLT 78.0±11.3 µm and CSLT mean rim area 1.07±0.18 mm2. CONCLUSIONS: In small optic discs, BMO-MRW and peripapillary RNFLT (OCT) have similar sensitivity to discriminate patients with glaucoma from normal controls; both exceed CSLT rim area in diagnostic power. In glaucomatous patients, BMO-MRW correlates strongest with visual field function.
EVALuna2:34195